Marketing in Fast Fashion: Greenwashing and Celebrities as Smokescreens - Chung, Kevin (Technium Social Sciences Journal, 2025)
Fast fashion—an industry defined by fast turnover rates and low prices—is projected to grow to a valuation of 29.1 billion USD by 2032 with a CAGR of 10.7%. As the fast fashion model dominates the industry, its dependence on international labor exploitation and its exponentially negative environmental impact continue to trouble consumers. Younger consumers in particular have widely expressed a commitment to ethical consumption and brand engagement. Nevertheless, these same consumers continue to support the growth of fast fashion. This paper first outlines the harms created by the fast fashion industry in regards to international labor exploitation and environmental degradation; then it investigates the marketing strategies used by fast fashion companies to continue to engage consumers. Greenwashing and the use of celebrities, in particular, are found to be effective in creating protective barriers around fast fashion companies, allowing them to continue exploitative practices while winning over consumers that profess a high valuation of ethical business practices in regards to both labor and sustainability.